PENGARUH TEKNIK DISTRAKSI IMAJINASI TERBIMBING MELALUI REFLEKSI WARNA HIJAU DALAM MENGATASI NYERI PADA LANSIA DENGAN PENYAKIT RHEMATIK DI PSLU KASIAN KABUPATEN - Zidny Nuris Yuhbaba; Megawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2017)
Distraction is distracting the client's attention to increase tolerance to pain. The purpose of using distraction techniques in nursing interventions is to divert or distract clients from pain, one of which is the imagination distraction technique. Imagination distraction techniques can be used to reduce pain. This technique uses the imagination of a person in a specially planned way, namely through green reflection to achieve a certain positive effect, which is to reduce pain. The purpose of this study was to determine the effect of guided imagination distraction techniques through green reflection in dealing with pain in the elderly with rheumatoid arthritis. This research uses one group pretest-postets design. The population in the study amounted to 60 elderly patients with rheumatoid arthritis in PSLU Kasian Jember District in 2015 with a sample of 53 elderly. In this study the guided imagination technique is given 1 time with a duration of 10 minutes. The data collection method uses Visual Analog Scale then the data is analyzed using a statistical T-test with the results of p value 0.00 <α 0.05. The conclusion of this study is that there is an influence of guided imagination distraction through green reflection on the level of pain in patients with rheumatic arthritis. The results showed that the guided imagination technique using green color reflection could be utilized as one of the nursing interventions in reducing pain levels